Author Correction: Ancient hepatitis B viruses from the Bronze Age to the Medieval period. (11th October 2018) - Muhlemann, Barbara; Jones, Terry; Barros Damgaard, Peter; Allentoft, Morten; Shevnina, Irina; Logvin, Andrey; Usmanova, Emma; Panyushkina, Irina; Boldgiv, Bazartseren; Bazartseren, Tsevel; Tashbaeva, Kadicha; Merz, Victor; et al.
In Fig. 2 of this Letter, the 'E' and 'G' clade labels were inadvertently reversed, and in Table 2 the genotype of DA27 was 'D1' instead of 'D5'. These have been corrected online.